2017
DOI: 10.1111/jan.13252
|View full text |Cite
|
Sign up to set email alerts
|

The difficulties experienced by nurses and healthcare staff involved in the process of breaking bad news

Abstract: The framework provides insights into the scope of the challenges faced by staff when they engage in the process of breaking bad news. This provides the foundation for developing interventions to support staff that more closely matches their experiences in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 24 publications
2
32
0
5
Order By: Relevance
“…Literature revealed that a major barrier for delivering bad news is lack of nurses' knowledge [25,26]. In this study, 67% of Jordanian critical care nurses stated that they face barrier during breaking bad news process, in which major barrier to nurses (73%) was not having time to do it.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Literature revealed that a major barrier for delivering bad news is lack of nurses' knowledge [25,26]. In this study, 67% of Jordanian critical care nurses stated that they face barrier during breaking bad news process, in which major barrier to nurses (73%) was not having time to do it.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, Lin et al [24] reported that the lack of communication training negatively affects nurses' perspective during communication with patients. Furthermore, Warnock, Buchanan and Tod [25] concluded that patients' diagnosis and treatment modalities could affect BBN process.…”
Section: Introductionmentioning
confidence: 99%
“…The findings also highlighted negative experiences of disclosing perceived bad news, and the impact on practitioners' emotional well-being [19]. This has been previously highlighted as a potential cause of work-related stress [10,11,19]. Both novice and experienced practitioners expressed relief their experiences resonated with others and expressed a desire for more formal and informal peer support to support their emotional well-being.…”
Section: Discussionmentioning
confidence: 74%
“…If done badly, it can impact on subsequent quality of life and well-being 9. Recent research indicated that considering BBN as a process involving multiple episodes of information provision and supportive interventions is a useful approach and can facilitate good practice 10 11. This is in comparison to emphasising the single episode of care when bad news, such as a diagnosis, is confirmed.…”
Section: Introductionmentioning
confidence: 99%